IMPLEMENTATION OF HALAL LABELIZATION IN THE PURCHASE DECISION OF WARDA PRODUCTS IN PP.LUBBUL-LABIB - Sinta Maulidia; Nur Lailatul Fitria (IJED: International Journal of Economy Development Research, 2023)
Halal label is part of the packaging on a product that contains information about the product or product sales. Halal label is an inclusion of a halal logo which aims as a statement of the halalness of the product. Product quality as the expected level of quality and control of diversity in achieving that quality to meet consumer needs. A product that has high quality will certainly give satisfaction to customers. decisions for Wardah products at muslimah PP Lubbul Labib and the quality moderates or significantly strengthens the relationship between halal labeling and purchasing decisions.          This research uses a quantitative approach. The data used is primary data and sample used was 15 people using the Slovin formula, taken by non-probability sampling with random sampling technique. The results of this study indicate that the halal labeling variable has a significant positive effect on purchasing          Products that have good quality are products that comply with specifications and provide satisfaction to consumers in meeting their needs. In addition, the halal label on the product is a distinctive feature for consumers as a guarantee of security in consuming the product, therefore, halal labeling and product quality will greatly influence purchasing decisions on products. In an Islamic perspective, it is necessary to include a halal label marked with halal certification. With the existence of halal certification, maslahah can be achieved and reassure the people. Maslahah in this case is maslahaha mursalah, namely the benefits that arise after the Muhammad SAW. died, and the maslahah is recognized and does not conflict with the shari'a.